Does trust in supervisors translate to compliance and cooperation? A test of internal procedural justice among Taiwanese police officers - Wang, Shun-Yung Kevin (The Australian and New Zealand journal of criminology, 2020)
The procedural justice model of policing has gained much popularity in scholarship and empirical support in democracies, yet research on the procedural justice within police organizations, particularly the mediating mechanisms connecting internal procedural justice and officer behavioral tendencies, is rather limited. With an aid of survey data collected from Taiwanese police officers, this study tests the connections between internal procedural justice and officers’ compliance with agency rules and cooperation with supervisors via an essential element—trust in supervisors. Internal procedural justice was found to be directly related to trust in supervisors and officer cooperation with supervisor, whereas the association between internal procedural justice and compliance with agency rules is mainly indirect through trust in supervisors. This study concludes with discussing research and pragmatic implications of findings.